2008
DOI: 10.1186/1471-2458-8-275
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hypertension prevalence, unawareness and treatment among Costa Rican elderly

Abstract: BackgroundReliable information on the prevalence of hypertension is crucial in the development of health policies for prevention, control, and early diagnosis of this condition. This study describes the prevalence of hypertension among Costa Rican elderly, and identifies co-factors associated with its prevalence, unawareness and treatment.MethodsThe prevalence of hypertension is estimated for the Costa Rican elderly. Measurement error is assessed, and factors associated with high blood pressure are explored. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
35
4
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 21 publications
13
35
4
14
Order By: Relevance
“…Another Singaporean study using the same definition of hypertension as we did, although not limited to the elderly, did report a prevalence of hypertension among those aged X65 years that was comparable with our findings. 6 Similar to previous studies, 14,[16][17][18]20,22,23,25,26 we observed hypertension to be associated with age, higher BMI and diabetes. We also observed elderly men to be at a higher risk of hypertension, whereas previous studies have reported either no association with gender, 17,20 or a higher risk for women.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Another Singaporean study using the same definition of hypertension as we did, although not limited to the elderly, did report a prevalence of hypertension among those aged X65 years that was comparable with our findings. 6 Similar to previous studies, 14,[16][17][18]20,22,23,25,26 we observed hypertension to be associated with age, higher BMI and diabetes. We also observed elderly men to be at a higher risk of hypertension, whereas previous studies have reported either no association with gender, 17,20 or a higher risk for women.…”
Section: Discussionsupporting
confidence: 80%
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations